Improving Quality of Experience (QoE) in Malay Language Autism Identification Assessment - Rahmad, Arieana (Multidisciplinary Applied Research and Innovation, 2023)
Autism can be described as "pervasive developmental disorder" that involves the functioning the part of the brain. Autism is considered a neurological disability and not a psychiatric disorder. Therefore, one purpose of this project is to develop a game-based learning application through visuals to attract interest and help autistic children to learn. Identifying Autism amongst Malaysian citizen especially children nowadays are a prominent issue. The usual practice of Autism screening test in the Malaysian school system is by teacher’s observation and intervention. This usually time consuming and less accurate. Moreover, Autism children enrolling in a normal education system will encounter many problems to the teacher and to the children itself. Therefore, a mobile-based application for Autism screening test named Kiddo Autism is developed. Multimedia elements as well as Gamification Based Learning are implemented in this application to enhance visual and auditory senses among children during screening test. Apart from that this application can be used as learning tool for Autism children to learn alphabet letter and phonic. A usability study has been conducted towards possible students with autism using Mean Opinion Score (MOS). Result from the study shows that 93% of respondents agreed that the application achieved its objectives and feel that the application able to enhance the QoE of children during the screening test.